2000
DOI: 10.1007/s004180000168
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of calcineurin and FKBP12, the FK506-binding protein, in Hassall's corpuscles of human thymus and epidermis

Abstract: Calcineurin, a Ca 2+ /calmodulin-dependent protein phosphatase, plays an important role in various physiological functions including T cell activation. This enzyme is a target molecule for the immunosuppressants, cyclosporin A and FK506. In the present study, we investigated immunohistochemical localization of calcineurin and FKBP12, an FK506-binding protein, in human thymus and epidermis. The catalytic subunit (calcineurin A) of calcineurin was abundantly expressed in Hassall's corpuscles which were localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…These proteins are target molecules for ciclosporin A and FK‐506. Their expressions are increased with the differentiation of keratinocytes 29 . On the other hand, ciclosporin A and FK‐506 inhibit keratinocyte proliferation induced by epidemal growth factor, transforming growth factor‐α and IL‐6 30 .…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are target molecules for ciclosporin A and FK‐506. Their expressions are increased with the differentiation of keratinocytes 29 . On the other hand, ciclosporin A and FK‐506 inhibit keratinocyte proliferation induced by epidemal growth factor, transforming growth factor‐α and IL‐6 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the actions of calcineurin inhibitors are not limited to T cells. NFAT1 expression was first described by Northrop et al (120) in mice skin, and then calcineurin expression was subsequently reported in the human epidermis (121). Calcineurin inhibitors reduce antigen presentation by Langerhans' cells and suppress neutrophil chemotaxis through the inhibition of psoriatic monocytes (122).…”
Section: Psoriasismentioning
confidence: 99%
“…In thymic epithelial cells that show many intriguing similarities to epidermal keratinocytes (67)(68)(69), overexpression of Wnt 4 or Wnt 5b is associated with an increase in Foxn1 mRNA levels, whereas this is not the case for Wnt 1 (70). This suggests that certain Wnt proteins regulate Foxn1 transcription in thymic epithelial cells and prompts investigations on the regulation of Foxn1 gene transcription in dependence of Wnt signaling in hair follicle keratinocytes where Wnt signaling is crucially implicated in morphogenesis and cycling (71) (Fig.…”
Section: Foxn1 and The Wnt Pathwaymentioning
confidence: 99%